The Effect of Administering A Combination of Bay Leaf Boiled Water and Honey on Decreasing Mean Arterial Pressure (MAP) in Prelaines with Hypertension - Rapika, Nor; Tasalim, Rian; Mahdiyah, Dede; Redjeki, Dwi Sogi Sri (Indonesian Journal of Global Health Research, 2024)
Hypertension is often referred to as a "silent killer" because it often arises without symptoms. Data from the World Health Organization (WHO) in 2022 that there are around 1.56 billion people around the world suffering from hypertension and it is estimated that the prevalence of hypertension will continue to increase from year to year. In Gambut District, Banjar Regency is the area with the highest incidence of hypertension from year to year. There are 2 ways of hypertension management, namely pharmacological management and non-pharmacological management. One example of non-pharmacological management is by giving a combination of bay leaf decoction water and honey. Objective to determine the effect of a combination of bay leaf and honey boiled water on the reduction of Mean Arterial Pressure (MAP) value in elderly people with hypertension in the working area of the Peat Health Center. This study used a quantitative method with a Pre-Experimental research design Two Group Pretest-Posttest Design. The number of samples was 30 respondents using the purposive sampling technique, which was tested by the Wilcoxon statistical test. The results of statistical analysis showed that there was a significant difference in MAP values between before and after the intervention of a combination of bay leaf and honey boiled water. There was an effect of giving a combination of bay leaf decoction and honey on MAP value.